PENURUNAN EKSISTENSI KAMPUNG PECINAN KEMBANG JEPUN (KYA-KYA) DI KOTA SURABAYA - , JOOBU WAHYUDI, M. Sani Roychansyah, S.T., M.Eng., D.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Revitalization ia an effort which have been given in the center of the city. The revitalization effort aims to revive the image of a degraded area. Kembang Jepun located in Surabaya, and is one of the old city area which has a long history of almost as old as Surabaya.On May 31, 2003 Kya-kya Kembang Jepun was the center of the court was food / drink, a variety of events and live music. To influence the outcome of the District (Kampoong) Kembang Jepun local residents. After a decline inthe region in an effort to get back to the year and it does not have the role in Surabaya. This research aims to identify the factors that Kya-kya Kembang Jepun was degraded and described as good tobe done before and after the program. The method used in this research is a case study with some proposition to be verified in the area. The approach used is qualitative and quantitative for explaining phenomena that exist and describing the development of the case. After conducting research, There are several several factors that degraded was District (Kampoong) Kembang Jepun (Kya-kya). Furthermore, the criteria have been compared with the success of the revitalization according to existing theories. It happens inequalities in revitalization success criteria, namely Kya-kya management conditions are not ready and not professional in the selection of incoming traders, and there is no support from the government. This resulted in a visitor area and surrounding communities District (Kampoong) Kembang Jepun (Kya-kya). Revitalization and development conducted in the area jepun not succeed and learning to be a revitalization of the village Chinatowns in other cities.